In vivo kinematic comparison of bi-cruciate retaining total knee arthroplasty between mechanical alignment and functional alignment methods - Tomofumi Kage; Kenichi Kono; Tetsuya Tomita; Takaharu Yamazaki; Shuji Taketomi; Ryota Yamagami; Kohei Kawaguchi; Ryo Murakami; Takahiro Arakawa; Takashi Kobayashi; Sakae Tanaka; Hiroshi Inui (Elsevier, 2024)
Background/objective: This study aimed to clarify the kinematics of bi-cruciate-retaining (BCR) total knee arthroplasty (TKA) by comparing the mechanical alignment (MA) and functional alignment (FA) methods and to evaluate differences between the two alignment methods. Methods: The in vivo kinematics of 20 MA TKA and 20 FA TKA knees were investigated under fluoroscopy during squatting using a two-to three-dimensional registration technique. Accordingly, knee flexion angle, axial rotational angle, varus-valgus angle, anteroposterior translation of the medial and lateral low contact points of the femoral component relative to the tibial component and kinematic pathway were evaluated. Results: No difference in the knee flexion angle was observed between the MA and FA TKA groups. Femoral external rotation was observed in both groups and no significant difference was observed. Significant varus alignment from extension to early flexion range was observed in the FA TKA group. The posterior translation of the medial side was smaller in the FA TKA group than in the MA TKA group. Conversely, no significant difference in the anteroposterior translation of the lateral side was observed. In the kinematic pathway, a medial pivot motion from 0° to 20° of flexion and a lateral pivot motion beyond 20° of flexion were observed in both groups. Conclusion: During squatting in BCR TKA, the FA TKA group significantly showed varus alignment and smaller posterior translation of the medial side than the MA TKA group from extension to early flexion range.